(untitled) (Journal of Enam Medical College, 2019)
Leptospirosis is a zoonosis with protean manifestation caused by the spirochete, Leptospira interrogans. Here we report a 60-year-old male who presented with sudden onset of fever, rigors, myalgia and headache occasionally accompanied by nausea, vomiting and diarrhea. Later during the course of treatment he developed encephalopathy with fulminant hepatic failure and acute kidney injury and was diagnosed as a case of leptospirosis. A timely workup combined with early initiation of antibiotics and hemodialysis led to effective treatment for this patient. J Enam Med Col 2019; 9(2): 136-139